2011
DOI: 10.19173/irrodl.v12i6.1018
|View full text |Cite
|
Sign up to set email alerts
|

Distance students’ readiness for social media and collaboration

Abstract: In recent years, there has been a rapid growth in the use of social networking tools (e.g., Facebook) and social media in general, mainly for social, recreational, and entertainment purposes (Smith, Salaway, & Caruso, 2009). Many educators believe that these tools offer new educational affordances and avenues for students to interact with each other and with their teachers or tutors. Considering the traditional dropout rate problem documented in distance courses (Rovai, 2003; Woodley, 2004), these tools may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 17 publications
0
19
0
3
Order By: Relevance
“…Some research has explored the extent to which students use particular social media tools. For instance, Poelhuber and Anderson (2011) examined the use of social media and other collaboration tools in the context of distance learning and found that males and younger students have more positive attitudes toward technology as well as greater experience with social media. Zula, Yarrish, and Pawelzik (2011) explored the use of social networking tools in business education and found that younger students (18-20 years old) spent less time on career exploration research than older students (21-24 years old) but found no significant difference with regard to time spent on social networks in general.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research has explored the extent to which students use particular social media tools. For instance, Poelhuber and Anderson (2011) examined the use of social media and other collaboration tools in the context of distance learning and found that males and younger students have more positive attitudes toward technology as well as greater experience with social media. Zula, Yarrish, and Pawelzik (2011) explored the use of social networking tools in business education and found that younger students (18-20 years old) spent less time on career exploration research than older students (21-24 years old) but found no significant difference with regard to time spent on social networks in general.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After considering software and hardware compatibility and access, student competency and comfort with technology must be addressed as it has been associated with the learning outcomes and student satisfaction (Moore, 2005;Poellhuber & Anderson 2011). Therefore, to facilitate improved learning outcomes and satisfaction, course design should include early and ongoing technological support for all students (Heale, Gorham & Fournier, 2010), contact information for technical support, integrated tutorials and e-links, as well as a list of menu items to navigate the site (Chou, 2003).…”
Section: Communication Technologiesmentioning
confidence: 99%
“…Pre-service researchers used information management tools, such as Monkey surveys and Google Docs, for data collection during the pandemic. Previous studies (3,31,32) showed that graduate students had frequently used information management tools, file sharing, research databases, and reference management tools to complete their research. The successful use of SM tools boosted the self-efficacy and transformed their negative attitudes into positive ones (20,33).…”
Section: Figure 2 Effect Of Social Media On Research Competences Andmentioning
confidence: 99%